Malaria vectors and transmission dynamics in coastal south-western Cameroon - Bigoga, Jude D (BioMed Central, 2007)
BACKGROUND: Malaria is a major public health problem in Cameroon. Unlike in the southern forested areas where the epidemiology of malaria has been better studied prior to the implementation of control activities, little is known about the distribution and role of anophelines in malaria transmission in the coastal areas. METHODS: A 12-month longitudinal entomological survey was conducted in Tiko, Limbe and Idenau from August 2001 to July 2002. Mosquitoes captured indoors on human volunteers were identified morphologically. Species of the Anopheles gambiae complex were identified using the polymerase chain reaction (PCR). Mosquito infectivity was detected by the enzyme-linked immunosorbent assay and PCR. Malariometric indices (plasmodic index, gametocytic index, parasite species prevalence) were determined in three age groups (<5 yrs, 5–15 yrs, >15 yrs) and followed-up once every three months. RESULTS: In all, 2,773 malaria vectors comprising Anopheles gambiae (78.2%), Anopheles funestus (17.4%) and Anopheles nili (7.4%) were captured. Anopheles melas was not anthropophagic. Anopheles gambiae had the highest infection rates. There were 287, 160 and 149 infective bites/person/year in Tiko, Limbe and Idenau, respectively. Anopheles gambiae accounted for 72.7%, An. funestus for 23% and An. nili for 4.3% of the transmission. The prevalence of malaria parasitaemia was 41.5% in children <5 years of age, 31.5% in those 5–15 years and 10.5% in those >15 years, and Plasmodium falciparum was the predominant parasite species. CONCLUSION: Malaria transmission is perennial, rainfall dependent and An. melas does not contribute to transmission. These findings are important in the planning and implementation of malaria control activities in coastal Cameroon and West Africa.